Fatal Pseudomonas aeruginosa pneumonia in a previously healthy woman was most likely associated with a contaminated hot tub. - Huhulescu, S.; Simon, M.; Lubnow, M.; Kaase, M.; Wewalka, G.; Pietzka, A.; Stöger, A.; Ruppitsch, W.; Allerberger, F. (Infection, 2011)
Community-acquired pneumonia due to Pseudomonas aeruginosa in previously healthy individuals is a rare disease that is associated with high fatality. On 14 February 2010 a previously healthy 49-year-old woman presented to an emergency room with signs and symptoms of pneumonia, 2 days after returning from a spa holiday in a wellness hotel. Blood cultures and respiratory specimens grew P. aeruginosa. Despite adequate antimicrobial therapy, the patient died of septic multiorgan failure on day nine of hospitalization. On February 26, nine water samples were taken from the hotel facilities used by the patient: In the hot tub sample 37,000 colony-forming units of P. aeruginosa/100 ml were detected. Two of five individual colonies from the primary plate used for this hot tub water sample were found to be genetically closely related to the patients' isolates. Results from PFGE, AFLP and MLST analysis allowed the two lung isolates gained at autopsy and the whirlpool bathtub isolates to be allocated into one cluster. The patient most likely acquired P. aeruginosa from the contaminated water in the hotel's hot tub. The detection of P. aeruginosa in high numbers in a hot tub indicates massive biofilm formation in the bath circulation and severe deficiencies in hygienic maintenance. The increasing popularity of hot tubs in hotels and private homes demands increased awareness about potential health risks associated with deficient hygienic maintenance.